The role of chitin, chitinases, and chitinase-like proteins in pediatric lung diseases - Mack, Ines; Hector, Andreas; Ballbach, Marlene; Kohlhäufl, Julius; Fuchs, Katharina J.; Weber, Alexander N. R.; Mall, Marcus A.; Hartl, Dominik (Molecular and Cellular Pediatrics, 2015)
Chitin, after cellulose, the second most abundant biopolymer on earth, is a key component of insects, fungi, and house-dust mites. Lower life forms are endowed with chitinases to defend themselves against chitin-bearing pathogens. Unexpectedly, humans were also found to express chitinases as well as chitinase-like proteins that modulate immune responses. Particularly, increased levels of the chitinase-like protein YKL-40 have been associated with severe asthma, cystic fibrosis, and other inflammatory disease conditions. Here, we summarize and discuss the potential role of chitin, chitinases, and chitinase-like proteins in pediatric lung diseases.
Gesehen am 04.06.2020